2015
DOI: 10.1371/journal.pone.0126741
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide Is Associated with a Future Diagnosis of Cancer in Patients with Coronary Artery Disease

Abstract: ObjectiveSeveral papers have reported elevated plasma levels of natriuretic peptides in patients with a previous diagnosis of cancer. We have explored whether N-terminal pro-brain natriuretic peptide (NT-proBNP) plasma levels predict a future diagnosis of cancer in patients with coronary artery disease (CAD).MethodsWe studied 699 patients with CAD free of cancer. At baseline, NT-proBNP, galectin-3, monocyte chemoattractant protein-1, soluble tumor necrosis factor-like weak inducer of apoptosis, high-sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
(47 reference statements)
2
19
2
Order By: Relevance
“…In this regard, although initially described in the brain, it is now known to be secreted by the ventricular myocardium [ 5 ], and it is being used for the diagnosis of heart failure [ 4 , 5 ], having also prognostic value in patients with cardiovascular disease [ 2 ]. More recently, NT-proBNP levels have been shown to increase in patients with cancer [ 34 37 ]. Given that natriuretic peptides have been shown to have antiproliferative effects [ 38 40 ] it has been hypothesized that NT-proBNP plasma levels could increase in response to the excessive cell proliferation present in cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, although initially described in the brain, it is now known to be secreted by the ventricular myocardium [ 5 ], and it is being used for the diagnosis of heart failure [ 4 , 5 ], having also prognostic value in patients with cardiovascular disease [ 2 ]. More recently, NT-proBNP levels have been shown to increase in patients with cancer [ 34 37 ]. Given that natriuretic peptides have been shown to have antiproliferative effects [ 38 40 ] it has been hypothesized that NT-proBNP plasma levels could increase in response to the excessive cell proliferation present in cancer [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, NT-proBNP levels have been shown to increase in patients with cancer [ 34 37 ]. Given that natriuretic peptides have been shown to have antiproliferative effects [ 38 40 ] it has been hypothesized that NT-proBNP plasma levels could increase in response to the excessive cell proliferation present in cancer [ 37 ]. Then, the possibility exists that NT-proBNP plasma levels could also increase in response to the cell proliferation present in atherosclerosis, and that theoretically should be especially important in cases of extensive and severe CAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, NT-pro BNP could have predictive power beyond cardiovascular risk [5]. In fact, this biomarker is associated with a higher risk of death in patients with cardiovascular diseases and in elderly subjects [7]. It is very helpful in the differential dia gnosis of dyspnoea.…”
Section: Nt-probnp and Natriuretic Factorsmentioning
confidence: 99%
“…ANP inhibits the amiloride-sensitive Na + /H + exchanger isoform 1, thus disrupting cancer cell pH homeostasis and reducing cell survival [ 49 , 50 , 51 ]. However, some groups [ 38 , 52 , 53 , 54 ] reported that plasma BNP levels are elevated in patients with cancer and suggested that these increases are due to the cardiac response to cancer-related inflammation. Indeed, BNP is upregulated at the transcriptional and translational levels by pro-inflammatory cytokines in myocardiocytes [ 55 ] and patients with hematologic malignancies have elevated levels of N-terminal –proBNP, related to a possible myocardium response to the setting of the cancer [ 56 , 57 ].…”
Section: Natriuretic Peptides and Cancermentioning
confidence: 99%
“…All the physiological effects of natriuretic peptide hormones are mediated by the interaction with the cell surface natriuretic peptide receptor A (NPRA; high affinity) and natriuretic peptide receptor C (NPRC; low affinity) [ 54 ]. ANP overexpression decreases NPRA levels in cells by a feedback inhibition.…”
Section: Natriuretic Peptides and Prostate Cancermentioning
confidence: 99%